Potential impact of the internet and E-commerce on selected service industries in the Caribbean - Henry, Lester (2001)
Examines the potential impact of the internet and E-commerce on various Caribbean service industries. Discusses the benefits and possible costs of E-commerce. Outlines some strengths and weaknesses of selected service sector industries. Deals with the issue of whether E-commerce and the internet enhance or undermine the development of the services sector in the Caribbean.